Laparoscopic Mesh-Less Cervicosacropexy for Uterovaginal Prolapse. Issue 6 (November 2018) - Seracchioli, Renato; Raimondo, Diego; Arena, Alessandro; Gava, Giulia; Parmeggiani, Clara; Martelli, Valentina; Moro, Elisa; Zanello, Margherita; Paradisi, Roberto; Mabrouk, Mohamed
Abstract : Objectives: This study aimed to evaluate surgical and clinical outcomes of laparoscopic mesh-less cervicosacropexy for the treatment of uterovaginal prolapse. Methods: This single institutional review board–approved prospective cohort study enrolled 46 consecutive, sexually active symptomatic women requiring surgical correction of uterovaginal prolapse, from July 2013 to March 2016. After supracervical laparoscopic hysterectomy, the cervix was suspended to the anterior longitudinal ligament of the sacral promontory through a continuous suture with plication and shortening of the right uterosacral ligament. Pelvic organs' function was evaluated through validated questionnaires during preoperative and postoperative follow-up evaluations. The anatomical recurrences of genital prolapse with a Pelvic Organ Prolapse Quantitative stage 2 or higher, in particular of central compartment (Pelvic Organ Prolapse Quantitative score C ≥−1), were recorded. Results: Mean ± SD age was 55.5 ± 10.9 years. Mean ± SD operating time was 97.4 ± 25.6 (range, 60–180) minutes. Mean ± SD hospitalization length was 3.6 ± 0.9 (range, 2–6) days. No intraoperative complications were recorded. Median length of follow-up was 24 (range, 12–38) months. During the follow-up period, the objective success rates for central compartment prolapse and for all compartments were 93.5% and 89.1%, respectively. No woman presented dyspareunia at follow-up. Thirty-nine women (84.8%) reported very high satisfaction related to surgery and 6 (13%) a moderate satisfaction. Overall Female Sexual Function Index, Knowles-Eccersley-Scott Symptom, and Bristol Female Lower Urinary Tract scores improved significantly after surgery, except for incontinence score domain. Conclusions: Laparoscopic mesh-less cervicosacropexy represents an effective and feasible option for the surgical treatment of uterovaginal prolapse in sexually active women, avoiding postoperative complications due to the mesh use. Abstract : Laparoscopic mesh-less cervicosacropexy represents an effective, safe, and feasible option for the surgical treatment of uterovaginal prolapse in sexually active women.